Penguatan Pendidikan Karakter Melalui Pembelajaran Berbasis Integrasi Iman, Ilmu, dan Amal di Sekolah: Perspektif Guru - Soleh, Warissuddin; Chalilullah, Chalilullah; Jufri, Salman (Indonesian Journal of Islamic Education and Local Culture, 2025)
This article covers matters related to the importance of strengthening character education in schools. Character education must not be separated from the learning process of teaching at school. To be a developed country, Indonesia needs the quality of human resources that are superior in terms of both knowledge, skills, and also character. This article aims to learn about the implementation of character education based on integration of faith, science, and charity in school, and to know the importance of strengthening character education as well as the factors that influence the character education process in school. The research was carried out by applying a method of qualitative approach through the process of interviewing a source who is a teacher of Islamic religion education to discuss related education character at school. The data analysis in this article is carried out through the data collection process based on the interview process that has been conducted, continued with data presentation and data processing, and ended with the drawing of conclusions. After the interview was conducted, it was concluded that strengthening character education through learning based on faith, science, and charity was vital to implement. It is a consideration that in school character education is the first solution to be able to create a good character of students in school, which is expected to be applied to students in all spheres of life.